Business community portal [electronic resource] (MERLOT, 1997)
Quoted from the homepage: Welcome to the Business Portal for MERLOT. The Business Editorial Board strives to provide valuable resources to help in your business teaching career. While our focus is on accounting, economics, management, and marketing, we provide materials for other business disciplines as well. Please join MERLOT and contribute to this growing community of business instructors by using the resources, submitting your own materials and assignments for evaluation, and sharing ideas to help you teach online and in the classroom. We also invite you to become a Business Peer Reviewer. Our board uses the MERLOT Peer Reviewer Form to evaluate teaching modules.